INTERNALISASI DAN AKTUALISASI NILAI-NILAI KEAGAMAAN DI MADRASAH IBTIDAIYAH AL-FATTAH MOJOLANGU KOTA MALANG - Maulaanaa ‘Abdul Ghofar; Ika Ratih Sulistiani; Devi Wahyu Ertanti (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The study is intended to introduce internalization and actualization of these religious values so that students will hold to religious teachings and be strong in faith when they grow up. The study involves qualitative methods, where documents are obtained from interviews, observations, and documentation. Analyzed through observation of documents, events, and conclusions. The results of this study indicate that students are able to internalize and actualize the religious values that have been devised and framed by teacher MI Al-Fattah Mojolangu of the unfortunate city. Introducing and practicing religious values becomes a prelude to learners.